OPTIMALISASI DESAIN DIDAKTIS MATERI PEMAHAMAN KONSEP PERBANDINGAN NILAI MELALUI IDENTIFIKASI DAN PENANGANAN LEARNING OBSTACLE - Haqq, Arif Abdul; Amaliyah, Nur; Wahid, Sirojudin; Solahudin, Iman (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2023)
This research aims to develop an effective didactic design to address students' learning obstacles in the concept of value ratios. A qualitative research method was employed, specifically utilizing Didactical Design Research. Data were collected through tests, interviews, observations, and documentation from 8th-grade students at MTs PUI Kancana who had studied the subject matter. The didactic design was based on the analysis of learning obstacles and trajectories, metapedadidactics, and retrospectives. Following the implementation of the instructional design in 7th-grade class A at MTs PUI Kancana, which had not received prior instruction on value comparison, a decrease in students' learning obstacles was observed. Although not all learning obstacles were eliminated, the didactic design effectively reduced the barriers encountered by the students. This research holds significant implications for instructional development. By employing the didactic design for value ratios, it provides an alternative approach to enhance students' understanding and mastery of value comparison concepts. Consequently, this study offers an accurate and comprehensive overview of the didactic design approach to address learning obstacles in the context of value comparison. The findings highlight the importance of employing effective didactic designs to improve learning outcomes in the domain of value ratios.